2007
DOI: 10.1017/s0950268807008096
|View full text |Cite
|
Sign up to set email alerts
|

Emerging fluoroquinolone and macrolide resistance ofCampylobacter jejuniandCampylobacter coliisolates and their serotypes in Thai children from 1991 to 2000

Abstract: This study investigated fluoroquinolone, macrolide resistances and serotype distributions among Campylobacter jejuni and Campylobacter coli isolated from children in Bangkok and rural settings during 1991-2000. Phenotypic identification, serotyping, and susceptibility testing were performed by standard microbiological procedures. The predominant serotypes of C. jejuni were Lior 36, 2 and 4 and of C. coli were Lior 8, 29 and 55. Resistance to nalidixic acid increased significantly during 1991-2000 and the frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
2
29
2
2
Order By: Relevance
“…In the current study, all isolates were susceptible or moderately susceptible to erythromycin. Unlike some surveillances (20,23,(28)(29)(30)(31)(32)(33)(34), we did not find macrolide-resistant strains.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the current study, all isolates were susceptible or moderately susceptible to erythromycin. Unlike some surveillances (20,23,(28)(29)(30)(31)(32)(33)(34), we did not find macrolide-resistant strains.…”
Section: Discussioncontrasting
confidence: 99%
“…However, for the empiric treatment of adults with suspected bacterial gastroenteritis, the preferred drug typically includes a fluoroquinolone (ciprofloxacin) because of its broad scope of efficacy against almost all enteric bacterial pathogens (16). However, acquired resistance to macrolides, fluoroquinolones and other most widely used antibiotics gives rise to a challenge in campylobacteriosis control worldwide (17)(18)(19)(20). In developing countries, various patterns of campylobacter susceptibility to antibiotics were described (21).…”
Section: Introductionmentioning
confidence: 99%
“…However, the resistance rate of C. jejuni (12.5z) observed in this study was greater than that previously reported for C. jejuni isolated from Thai children with diarrhea between 1991 and 2000 (from 0z to 6.3z in 1999) (8,15). This further confirms recent concerns of the increase in macrolide resistance of C. jejuni in Thailand.…”
supporting
confidence: 79%
“…High-level resistant isolates carry a point mutuation (A2075G) in domain V of 23S rRNA, which is not observed in low-level resistant isolates (6). Currently, in addition to increasing widespread resistance of Campylobacter to fluoroquinolone, resistance to macrolides has been increasing in some countries (7,8). The aim of this study was to investigate the resistance of C. jejuni and C. coli isolated from Thai and Japanese children with diarrhea to fluoroquinolones and macrolides.…”
mentioning
confidence: 99%
“…Various reports around the world associate Campylobacter sp. infections resistant to fluoroquinolones with the approval of the use of this antimicrobial in poultry production (SERICHANTALERGS et al, 2007). Rastall (2004) investigated alternative antibiotics sources for campylobacteriosis treatment and found that the use of a probiotic (Lactobacillus acidophilus) together with a prebiotic (fructooligosaccharides, and lactosucrose) showed positive effects on the balance of intestinal microflora, an there was an improvement in recovery from infection and immune status.…”
Section: Treatmentmentioning
confidence: 99%